2012
DOI: 10.3892/etm.2012.623
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity assay for the diagnosis of malignant pleural effusion: A meta-analysis

Abstract: The telomerase activity assay has been established for the detection of malignant pleural effusion (MPE), however, the overall diagnostic accuracy of the telomerase activity assay for MPE remains unclear. We performed a systematic search in the Pubmed, Embase and Cochrane databases to identify published studies that have evaluated the diagnostic role of the telomerase activity assay for MPE. Sensitivity, specificity and other measures of accuracy of the telomerase activity assay in the diagnosis of MPE were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…A candidate target for such a marker is telomerase. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Telomerase provides a mechanism for cell immortalization and plays an important role in carcinogenesis. [21][22][23] Using an in situ version of the original Telomere Repeat Amplification Protocol (TRAP) assay, 24 TRAP in situ, 25 we have previously found that telomerase is a good marker for malignancy in effusions, strong nuclear reactivity being specific for malignant cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A candidate target for such a marker is telomerase. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Telomerase provides a mechanism for cell immortalization and plays an important role in carcinogenesis. [21][22][23] Using an in situ version of the original Telomere Repeat Amplification Protocol (TRAP) assay, 24 TRAP in situ, 25 we have previously found that telomerase is a good marker for malignancy in effusions, strong nuclear reactivity being specific for malignant cells.…”
mentioning
confidence: 99%
“…A candidate target for such a marker is telomerase . Telomerase provides a mechanism for cell immortalization and plays an important role in carcinogenesis .…”
mentioning
confidence: 99%